MLL2 and KDM6A mutations in patients with Kabuki syndrome. Issue 9 (2nd August 2013) - Miyake, Noriko; Koshimizu, Eriko; Okamoto, Nobuhiko; Mizuno, Seiji; Ogata, Tsutomu; Nagai, Toshiro; Kosho, Tomoki; Ohashi, Hirofumi; Kato, Mitsuhiro; Sasaki, Goro; Mabe, Hiroyo; Watanabe, Yoriko; et al.
Abstract Kabuki syndrome is a congenital anomaly syndrome characterized by developmental delay, intellectual disability, specific facial features including long palpebral fissures and ectropion of the lateral third of the lower eyelids, prominent digit pads, and skeletal and visceral abnormalities. Mutations in MLL2 and KDM6A cause Kabuki syndrome. We screened 81 individuals with Kabuki syndrome for mutations in these genes by conventional methods (n = 58) and/or targeted resequencing (n = 45) or whole exome sequencing (n = 5). We identified a mutation in MLL2 or KDM6A in 50 (61.7%) and 5 (6.2%) cases, respectively. Thirty‐five MLL2 mutations and two KDM6A mutations were novel. Non‐protein truncating‐type MLL2 mutations were mainly located around functional domains, while truncating‐type mutations were scattered through the entire coding region. The facial features of patients in the MLL2 truncating‐type mutation group were typical based on those of the 10 originally reported patients with Kabuki syndrome; those of the other groups were less typical. High arched eyebrows, short fifth finger, and hypotonia in infancy were more frequent in the MLL2 mutation group than in the KDM6A mutation group. Short stature and postnatal growth retardation were observed in all individuals with KDM6A mutations, but in only half of the group with MLL2 mutations. © 2013 Wiley Periodicals, Inc.